Modeling and optimization of jojoba oil extraction yield using Response Surface Methodology - Iyad Al-Sheikh; Jehad A.A. Yamin (GarVal Editorial Ltda., 2019)
Context: Jordan is looking for a cheap and locally affordable source for its cosmetics, fuel and medical applications. Jojoba offers one solution to such problems. It is considered as a good medicinal plant that can be used for several applications. Aims: To evaluate the effect of parameters as mixing speed, temperature, feedstock grain size, mixture ratio and mixing time on the jojoba yield. Methods: The mathematical model combining the effect of all the above variables was then used to find the optimum combination for maximum yield. Response Surface Methodology (RSM) technique was used for modeling and optimization. Based on the Pareto chart of parameters effect, the seed size was the most significant followed with temperature effect. Results: It was found that the optimum values obtained for best yield were seed size of about 0.48 mm, the temperature of about 65°C and mixing time of 2.8 hours maximum yield of about 56% wt can be obtained. Conclusions: A mathematical model was successfully built and tested for the Jojoba oil yield under different conditions. The optimum parameters that produced the highest yield were also found.